Emergence of dynamic phases in the presence of different kinds of open boundaries in stochastic transport with short-range interactions. (28th January 2016) - Nagel, Hannes; Janke, Wolfhard
Abstract: We discuss the effects of open boundary conditions and boundary induced drift on condensation phenomena in the pair-factorized steady states transport process, a versatile model for stochastic transport with tunable nearest–neighbour interactions. Varying the specific type of the boundary implementation as well as the presence of a particle drift, we observe phase diagrams that are similar but richer compared to those of the simpler zero-range process with open boundary conditions. Tuning our model towards zero-range-process-like properties we are able to study boundary induced effects in the transition regime from zero-range interactions to short-range interactions. We discuss the emerging phase structure where spatially extended condensates can be observed at the boundaries as well as in the bulk system and compare it to the situation with periodic boundaries, where the dynamics leads to the formation of a single condensate in the bulk.